2012
DOI: 10.1182/blood-2012-05-402784
|View full text |Cite
|
Sign up to set email alerts
|

The role of miRNAs in the pathogenesis and diagnosis of B-cell lymphomas

Abstract: There is a demand to understand B-cell lymphoma pathogenesis better, to identify new markers, and to define multiple lymphoproliferative disorders more accurately. MicroRNAs (miRNAs) are regulators of protein translation, comprising a group of more than 1500 short noncoding single-strand RNA molecules of approximately 22 nucleotides in length. They are easily detectable in fresh or paraffinembedded diagnostic tissue and serum. Expression of individual miRNAs and miRNA signatures allows specific celldifferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 124 publications
(150 reference statements)
0
46
0
Order By: Relevance
“…Downregulation of a subset of miRNAs is a commonly observed feature of cancers, suggesting that these miRNAs, such as miR-548m, may act as tumor suppressors. Recent studies revealed that c-Myc activation resulted in widespread direct repression of miRNA expression and c-Myc-induced miRNA repression contributes to lymphoma aggressive progression (43)(44)(45). The stroma-induced miR-548m repression can be the result of c-Myc overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of a subset of miRNAs is a commonly observed feature of cancers, suggesting that these miRNAs, such as miR-548m, may act as tumor suppressors. Recent studies revealed that c-Myc activation resulted in widespread direct repression of miRNA expression and c-Myc-induced miRNA repression contributes to lymphoma aggressive progression (43)(44)(45). The stroma-induced miR-548m repression can be the result of c-Myc overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that highly proliferative lymphomas like BL or specific cases of MM 112 may be excellent case scenarios for therapeutic targeting of this pathway with rapamycin or its derivatives. 113 3) Playing a key role in downstream signaling from BCR, TLR and other co-receptors, NF-kB activity seems to be deregulated in the majority of B-cell lymphomas, although J.P. Vaqué et al 228 haematologica | 2014; 99 (2) © F e r r a t a S t o r t i F o u n d a t i o n specific features of activation and potential inhibition may differ among specific entities and even tumor subgroups. Deregulated NF-kB can be elicited by the numerous activating mutations found in NF-kB upstream regulators including those found in MYD 88 (in CLL, DLBCL, LPL) or in NIK/TNFAIP3 in SMLZ, to name but a few.…”
Section: Discussionmentioning
confidence: 99%
“…1 Moreover, specific gene expression and miRNA profiling signatures have also helped to distinguish between particular tumor types as the consequence of the deregulation of specific genes or pathways. 2 In addition to this, we now know that signaling from the B-cell receptor 3,4 and co-receptors (CD19, Toll-like receptors) 5,6 can be considered as triggers for activating critical signaling pathways that regulate a range of biological activities in B-cell lymphomas, including altered metabolism, 7 enhanced proliferation and survival, 1 and cell migration in response to soluble factors. 8 These highlight the increasing interest in developing BCR downstream signaling inhibitors with the potential for use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…At present, over 4,500 miRNAs have been identified in humans, and it is known that nearly all human protein-encoding genes can be controlled by miRNAs in both healthy and malignant cells. Abnormal expression of miRNA is now known to occur in many cancers, including malignant lymphomas (MLs) [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In B-cell lymphomas, molecular-based classifications of the subtypes have been successfully conducted, leading to the development of understanding of their pathogenesis. Subtype-based miRNA classification has also been successfully conducted in B-cell lymphomas [11][12][13][14]. In T-cell lymphomas, however, attempts at translocation-or molecular-based classification have been unsuccessful to date, and as a result, understanding of molecular-based pathogenesis of T-cell lymphoma has been insufficiently established.…”
Section: Introductionmentioning
confidence: 99%